Differences in Premenopausal Syndrome Between Users of Hormonal and Non-Hormonal Contraceptive Methods (LPPM Universitas PGRI Adi Buana Surabaya, 2025)
Premenopause, menopause, and postmenopause are three phases that women will experience when they are aged 40 to 50 years. The menopause phase is usually preceded by the premenopause phase. This study aims to determine the difference in premenopause syndrome between hormonal and non-hormonal contraceptive acceptors. The research design used was an analytic survey research design with a cross-sectional approach. The number of samples in this study was hormonal and non-hormonal contraceptive acceptors, selected using purposive sampling. The data analysis used was the Paired Sample t-Test. The results showed that the majority of hormonal contraceptive acceptors were in the